THE ROLE OF PERFORMANCE EVALUATION OF WORK DISCIPLINE AND ORGANIZATIONAL CULTURE ON EMPLOYEES PRODUCTIVITY OF GUDEG YU DJUM YOGYAKARTA - Ignatius Soni Kurniawan; Yosefina Evasentia (Universitas Muhammadiyah Makassar, 2022)
This study aims to determine the effect of employee performance evaluation, work discipline, and organizational culture on work productivity. The population used in this study are employees who work at Gudeg Yu Djum Yogyakarta. The sampling technique used in this study used accidental sampling. The data were taken by survey using a questionnaire and processed using multiple linear regression analysis. Employee performance evaluation and organizational culture were found to have a positive and significant effect on employee productivity. Work discipline has no significant effect on employee work productivity. Company leaders can improve performance evaluation indicators and culture that is still low to strengthen work productivity.